2007
DOI: 10.1186/1471-2121-8-13
|View full text |Cite
|
Sign up to set email alerts
|

The OXR domain defines a conserved family of eukaryotic oxidation resistance proteins

Abstract: Background: The NCOA7 gene product is an estrogen receptor associated protein that is highly similar to the human OXR1 gene product, which functions in oxidation resistance. OXR genes are conserved among all sequenced eukaryotes from yeast to humans. In this study we examine if NCOA7 has an oxidation resistance function similar to that demonstrated for OXR1. We also examine NCOA7 expression in response to oxidative stress and its subcellular localization in human cells, comparing these properties with those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 36 publications
1
79
0
Order By: Relevance
“…The TLDc domain is of undetermined function, though a recent paper suggests its involvement in protection from oxidative damage (Durand et al 2007). Moreover, previous studies of the yeast Oxr1 gene, which also contains a TLDc domain, indicate that it functions to protect cells from oxidative damage (Volkert et al 2000, Elliott & Volkert 2004.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The TLDc domain is of undetermined function, though a recent paper suggests its involvement in protection from oxidative damage (Durand et al 2007). Moreover, previous studies of the yeast Oxr1 gene, which also contains a TLDc domain, indicate that it functions to protect cells from oxidative damage (Volkert et al 2000, Elliott & Volkert 2004.…”
Section: Discussionmentioning
confidence: 99%
“…The only domain that is common to both Ncoa7 and Ncoa7B is the TLDc, which consists the major portion of Ncoa7B (59-221 aa). This domain is of undetermined function, though a recent paper suggests its involvement in protection from oxidative damage (Durand et al 2007). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCoA7 protein contains similar functional domains to the mitochondrial OXR1-protein, which is known to reduce oxidative damage in DNA structure. In contrast to OXR-1, NCoA7 is not stress-induced but reacts to estrogens and interacts with the estrogen receptor (10). Given that NCoA7 is not estrogen receptor-specific but binds to other nuclear receptors as well, this coactivator is involved in a variety of other signalling pathways (7,19).…”
Section: Allele Positivity Allele Positivity Genotype Frequencymentioning
confidence: 99%
“…Certain studies have indicated that NCoA7 may be a favourable prognostic indicator for neuroblastomas. On the other hand, other authors identified an isoform that appears to be ovulation-associated and reproduction system-specific; another study found NCoA7 to possess an activity that contributes to oxidation resistance (8,9,10). Given that NCoA7 is expressed in the mammary gland and thus plays a role in the response of this tissue to estrogens, molecular alterations in the NCoA7 protein may affect breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%